Immunization status and re-immunization of childhood acute lymphoblastic leukemia survivors - Ersin Toret; Sumeyye Emel Yel; Murat Suman; Yeter Duzenli Kar; Zeynep Canan Ozdemir; Meltem Dinleyici; Ozcan Bor (Taylor & Francis Group, 2021)
Intensive chemotherapy can cause long-lasting immunosuppression in children who survived cancer. The immunosuppression varies according to the type of cancer, intensity of chemotherapy and age of the patient. A sufficient immune reconstruction when has been completed in childhood cancer survivors, the re-vaccination program can achieve sufficient antibody levels for some of the life-threatening vaccine-preventable infectious diseases. This study evaluates the serological status of pediatric acute lymphoblastic leukemia (ALL) cases before and after the intensive chemotherapy treatment. Antibodies against measles, mumps, rubella, varicella, hepatitis A and B were tested with the enzyme-linked immunosorbent assay (ELISA) method. Antibody titers were measured firstly at the leukemia diagnosis time when the chemotherapy was not started. The second evaluation of antibody titers was studied at 6 months after the cessation of chemotherapy for all patients. Forty-six patients with the mean age of 6.1 ± 4.5 years were participated in this study. Changing to seronegative after treatment was significantly different in measles, rubella, hepatitis A and hepatitis B (p < .05). Seventy-eight (28%) antibody levels in the patients were non-protective for all diseases. Only three (7%) patients had protective antibody levels for all diseases in the sixth month of chemotherapy cessation. There was a negative correlation between patient's age and losing protective antibody levels for any vaccine-preventable disease (p < .05). Antibody levels against vaccine-preventable diseases have evident that reduced after ALL treatment at childhood. Pediatric ALL survivors must be re-vaccinated for vaccine-preventable diseases after achieving immune reconstruction.